Double-ion gradient doped lithium-rich manganese-based layered transition metal oxide as well as preparation method and application thereof

By using dual ion gradient doping technology in lithium-rich manganese-based layered transition metal oxides, the metal element M is doped to form the chemical structure of xLi2MnO3·(1-x)LiTM1-yMyO2, the lithium-rich layered transition metal oxidation is solved. The cycling performance of the substance in lithium-ion batteries is degraded and voltage attenuation problems, achieving high capacity and good cycling performance.

CN119447225AActive Publication Date: 2025-02-14GUANGDONG UNIV OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411454195.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-14
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

Lithium-rich layered transition metal oxides have serious problems such as degradation in cycle performance and voltage attenuation in lithium-ion batteries, which limit their commercial application.

Method used

The lithium-rich manganese-rich base layered transition metal oxide is used to modify the material by adding metal elements M (such as Sn, Mg, Ba, Ce) to the lithium-rich layered transition metal oxide to form xLi2MnO3· (1-x) Chemical structure of LiTM1-yMyO2. The method includes mixing the transition metal compound precursor with the metal compound solution, adjusting the pH value, and producing a doped material by high temperature treatment.

Benefits of technology

Achieve high first-time Coulomb efficiency, high capacity and excellent cycle performance. When the voltage window is 2~4.8V and the current density is 200mA/g, the specific capacity can reach 235mAh/g, and the capacity retention rate after 150 cycles. More than 95.3%, significantly improving the cycling properties and electrochemical stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447225A_ABST
    Figure CN119447225A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and discloses a double-ion gradient doped lithium-rich manganese-based layered transition metal oxide as well as a preparation method and application thereof. The chemical formula of the oxide is xLi2MnO3. (1-x) LiTM1-yMyO2, TM is more than one of Mn, Ni, Co, Fe or Cr, M is Sn and one of Mg, Ba, Zn or Ce, x is more than or equal to 0.01 and less than or equal to 0.5, y is more than or equal to 0.01 and less than or equal to 0.3, and y is more than or equal to 0.01 and less than or equal to 0.3. The dual-ion gradient doped lithium-rich manganese-based layered transition metal oxide has the advantages of high initial coulombic efficiency, high capacity and excellent cycle performance. When the voltage window is 2-4.8 V and the current density is 200 mA / g, the specific capacity can reach 235 mAh / g, the capacity retention ratio after 150 times of circulation is higher than 95.3%, and the composite material can be applied to the field of lithium ion batteries or power batteries as a positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and more specifically, relates to a dual-ion gradient doped lithium-rich manganese-based layered transition metal oxide, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of long service life, large specific energy, high efficiency of charge and discharge, and strong safety performance. They are widely used in mobile phones, laptops, cameras, electric vehicles, energy storage grids and other fields. According to the Outline of the National New Energy Development Plan, the rapid development of new energy electric vehicles requires lithium-ion power batteries with high energy density and power density. The high cost of positive electrode materials in lithium-ion power batteries has always been the key factor restricting the improvement of the energy density of power lithium-ion batteries. Therefore, the key to promoting new energy vehicles in my country lies in improving the energy density of power batteries and promoting their rapid development, and the key to improving the energy density of power batteries lies in the research and development of new positive electrode materials with high specific capacity or the modification of existing positive electrode materials.

[0003] At present, the energy density of the popular cathode materials on the market, such as lithium cobalt oxide, ternary materials, and lithium iron phosphate, cannot meet the market's demand for high energy density cathode materials, which has hindered the promotion of electric vehicles and the advancement of the national new energy development plan. Lithium-rich layered transition metal oxides have high specific capacity (theoretical capacity exceeds 250mAh g -1 ), high operating voltage, and low cost have become hotspots in the research and development of new energy sources at home and abroad. However, there are still some problems that need to be solved as positive electrode active materials for lithium-rich layered transition metal oxides. During the first charge and discharge, the Li2MnO3 component is activated, causing an irreversible structural rearrangement of the material particle structure, resulting in a loss of reversible capacity of the battery; spinel structure transformation occurs during the cycle, resulting in a loss of capacity; oxidation reaction of the material lattice oxygen occurs, releasing oxygen, causing the material structure to collapse; the material is easily corroded by the electrolyte at high potential. The combined effect of the above factors has caused lithium-ion batteries using lithium-rich layered transition metal oxides to suffer from serious problems such as decreased cycle performance and voltage decay during use, which has seriously limited their practical commercial applications. At present, researchers generally use strategies such as doping, coating, and crystal surface regulation to improve the first coulombic efficiency and cycle performance of lithium-rich materials and alleviate voltage decay. However, it is difficult to achieve sufficiently good results by using any of the above strategies alone for modification. Summary of the invention

[0004] In order to solve the above shortcomings and deficiencies, the primary purpose of the present invention is to provide a dual ion gradient doped lithium-rich manganese-based layered transition metal oxide, which has a high first coulombic efficiency, a high capacity, and excellent cycle performance. When the voltage window is 2 to 4.8V and the current density is 200mA / g, the specific capacity can reach 235mAh / g, and the capacity retention rate after 150 cycles is higher than 95.3%.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned dual ion gradient doped lithium-rich manganese-based layered transition metal oxide. The doping modification in this method refers to adding a metal element M to the lithium-rich layered transition metal oxide to replace part of the position of one or more elements in Mn and Ni.

[0006] Another object of the present invention is to provide an application of the above-mentioned dual ion gradient doped lithium-rich manganese-based layered transition metal oxide.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A dual ion gradient doped lithium-rich manganese-based layered transition metal oxide with the chemical formula xLi2MnO3·(1-x)LiTM 1-y M y O2, TM=one or more of Mn, Ni, Co, Fe or Cr, M=Sn and one of Mg, Ba, Zn or Ce, 0.01≤x≤0.5, 0.01≤y≤0.3.

[0009] Furthermore, the lithium-rich manganese-based layered transition metal oxide is prepared by uniformly mixing a transition metal compound precursor with a metal compound solution, adjusting the pH value of the mixed solution to 8 to 10 using an alkaline solution and continuously stirring, and obtaining a powder through washing, filtering, and drying; heating the powder to 500 to 800° C., naturally cooling to room temperature, adding a lithium source and mixing uniformly, heating the mixture to 800 to 1000° C., and naturally cooling to room temperature.

[0010] Preferably, the metal compound solution is a mixed aqueous solution of Na2SnO4 and one of MgSO4, BaSO4, ZnSO4, and CeSO4.

[0011] Preferably, the transition metal compound precursor is a transition metal carbonate or a transition metal hydroxide; the particle size of the transition metal compound precursor is 5 to 10 μm.

[0012] More preferably, the transition metal carbonate is one or more of MnCO3, NiCO3, CoCO3, FeCO3 or CrCO3; the transition metal hydroxide is one or more of Mn(OH)2, Ni(OH)2, Co(OH)2, Fe(OH)2 or Cr(OH)2.

[0013] Preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium fluoride, lithium chloride or lithium nitrate.

[0014] Preferably, the molar ratio of the transition metal compound precursor to Li in the lithium source is 1:(1-10); the molar ratio of the transition metal compound precursor to the metal compound solution is 100:(0.1-5).

[0015] Preferably, the alkaline solution is one or more of aqueous ammonia, aqueous sodium carbonate solution or aqueous sodium bicarbonate solution.

[0016] The preparation method of the dual ion gradient doped lithium-rich manganese-based layered transition metal oxide comprises the following specific steps:

[0017] S1. The transition metal compound precursor and the metal compound solution are mixed uniformly, and the pH of the mixed solution is adjusted to 8 to 10 with an alkaline solution, stirred for 30 to 240 minutes, filtered and washed, and dried at 100 to 150 ° C to obtain a powder;

[0018] S2. The powder is heated to 500-800°C and kept warm for 2-6 hours, then cooled to room temperature, a lithium source is added and mixed evenly, and then the mixture is heated to 800-1000°C and kept warm for 10-16 hours to obtain a dual-ion gradient doped lithium-rich manganese-based hierarchical transition metal oxide.

[0019] The dual-ion gradient doped lithium-manganese-rich layered transition metal oxide is used in the field of lithium-ion batteries or power batteries.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The dual-ion gradient doped lithium-rich manganese-based layered transition metal oxide of the present invention has slow capacity decay and excellent cycle performance, overcoming the shortcomings of the current lithium-rich oxide positive electrode materials with poor cycle performance and fast capacity decay. When the voltage window is 2.0-4.8V and the current density is 200mA / g, the specific capacity can reach 235mAh / g, and the capacity retention rate after 150 cycles is higher than 95%, which can be used as a positive electrode material in the field of lithium-ion batteries or power batteries.

[0022] 2. The metal ion concentration of the double-ion gradient-doped lithium-manganese-rich layered transition metal oxide of the present invention changes gradiently from the surface to the center of the material particles. The positive electrode material has the advantages of high specific capacity, simple synthesis process, easy control, good repeatability, etc., and has great commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM photograph of the dual ion gradient doped lithium-manganese-based layered transition metal oxide powder in Example 1.

[0024] Figure 2 The X-ray diffraction patterns of the dual ion gradient doped lithium manganese-based layered transition metal oxide powders in Examples 1-3 and the lithium manganese-based layered transition metal oxide in Comparative Example 1.

[0025] Figure 3 The double ion gradient doped lithium-rich manganese-based layered transition metal oxide powders of Examples 1-3 and the lithium-manganese-based layered transition metal oxide of Comparative Example 1 were used as positive electrodes at room temperature. -1 The first charge and discharge curve at .

[0026] Figure 4 The double ion gradient doped lithium-rich manganese-based layered transition metal oxide powders of Examples 1-3 and the lithium-manganese-based layered transition metal oxide of Comparative Example 1 were used as positive electrodes at room temperature at 200 mA g. -1 Capacity stability curve. DETAILED DESCRIPTION

[0027] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0028] Example 1

[0029] Weigh 0.96 g of transition metal carbonate precursor (Mn 0.75 Ni 0.25CO3) was dispersed in 50mL of deionized water to obtain solution A; 0.0254g Na2SnO4 and 0.0111g MgSO4 were weighed and dissolved in 25mL of deionized water to obtain solution B and solution C, and solution B and solution C were slowly added dropwise to the stirred solution A, and the pH of the mixed solution was adjusted to 8 with ammonia water, and then stirred for 30min, washed, filtered, and dried in an oven at 120°C to obtain powder D; after heating powder D to 500°C and keeping it warm for 3h, 0.45g lithium carbonate was added and heated at 800°C for 12h to obtain a magnesium-tin dual ion gradient doped lithium-rich manganese-based layered transition metal oxide, namely 0.5Li2MnO3·0.5LiMn 0.99 Ni 0.99 Mg 0.01 Sn 0.01 O2.

[0030] Figure 1 This is a SEM photo of the target product powder in this embodiment. Figure 1 It can be seen that the synthesized powder particles are round and uniform, with an average spherical diameter of about 4 microns.

[0031] Example 2

[0032] Weigh 0.96 g of transition metal carbonate precursor (Mn 0.75 Ni 0.25 CO3) was dispersed in 50mL of deionized water to obtain solution A; 0.0254g Na2SnO4 and 0.0154g BaSO4 were weighed and dissolved in 25mL of deionized water to obtain solution B and solution C, and solution B and solution C were slowly added dropwise to the stirred solution A, and the pH of the mixed solution was adjusted to 8.0 with ammonia water, and then stirred for 30min, washed, filtered, and dried in an oven at 120°C to obtain powder D; after heating powder D to 500°C and keeping it warm for 3h, 0.45g lithium carbonate was added and heated at 800°C for 12h to obtain barium-tin dual ion gradient doped lithium-rich manganese-based layered transition metal oxide, namely 0.5Li2MnO3·0.5LiMn 0.99 Ba 0.99 Sn 0.01 Mg 0.01 O2.

[0033] Example 3

[0034] Weigh 0.96 g of transition metal carbonate precursor (Mn 0.75 Ni 0.25CO3) was dispersed in 50 mL of deionized water to obtain solution A, 0.0254 g of Na2SnO4 and 0.0172 g of CeSO4 were weighed and dissolved in 25 mL of deionized water respectively to obtain solution B and solution C, solution B and solution C were slowly added dropwise to the stirred solution A, and the pH of the mixed solution was adjusted to 8 with ammonia water, and then stirred for 30 min, washed, filtered, and dried at 120 ° C to obtain powder D; after heating powder D to 600 ° C for 2.5 h, 0.45 g of lithium carbonate was added, and heated at 1000 ° C for 10 h to obtain cerium-tin dual ion gradient doped lithium-rich manganese-based layered transition metal oxide, that is, 0.5Li2MnO3·0.5LiMn 0.99 Ni 0.99 Ce 0.01 Sn 0.01 O2.

[0035] Comparative Example 1

[0036] Weigh 0.96 g of transition metal carbonate precursor (Mn 0.75 Ni 0.25 CO3) was dispersed in 100 mL of deionized water to obtain solution A, and the pH of the solution A was adjusted to 8 with ammonia water, then stirred for 30 min, washed, filtered, and dried in an oven at 120° C. to obtain powder D; the powder D was heated to 500° C. and kept warm for 3 h, and then 0.45 g of lithium carbonate was added, and heated at 800° C. for 12 h to obtain a lithium-rich manganese-based layered transition metal oxide, namely 0.5Li2MnO3·0.5LiMnNiO2.

[0037] Figure 2 The X-ray diffraction patterns of the lithium-manganese-based layered transition metal oxide powders doped with dual ion gradients in Examples 1-3 and the lithium-manganese-based layered transition metal oxide in Comparative Example 1. Figure 2 It can be seen that the powders prepared from Examples 1-3 are pure lithium-rich oxide crystalline phases.

[0038] The button cell was used for testing. The double ion gradient doped lithium-rich manganese-based layered transition metal oxide powder prepared in Example 1-3 was mixed with conductive carbon black and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 to form an electrode. The metal lithium sheet was used as the counter electrode. 1 mol·L -1 LiPF6 / EC+DMC+EMC (EC:DMC:EMC volume ratio 1:1:1) is used as electrolyte, polypropylene material is used as separator, battery test system is Xinwei, charge and discharge voltage window is 2.0~4.8V, charge and discharge current density is selected as 20mAg -1 and 200mAg -1 . Figure 3The double ion gradient doped lithium-rich manganese-based layered transition metal oxide powders of Examples 1-3 and the lithium-manganese-based layered transition metal oxide of Comparative Example 1 were used as positive electrodes at room temperature. -1 The first charge and discharge curve at . Figure 3 It can be seen that after 100 charge and discharge cycles, the discharge specific capacity of the dual ion gradient doped lithium-rich manganese-based layered transition metal oxide prepared in Examples 1-3 decays very slowly. -1 The charge and discharge current density at the current density is 221 mAh g -1 and 235mAhg -1 . Figure 4 The double ion gradient doped lithium-rich manganese-based layered transition metal oxide powders of Examples 1-3 and the lithium-manganese-based layered transition metal oxide of Comparative Example 1 were used as positive electrodes at room temperature at 200 mA g. -1 Capacity stability curve. Figure 4 It can be seen that after 150 charge and discharge cycles, the discharge capacity of the double ion gradient doped lithium-rich manganese-based layered transition metal oxide powder as the positive electrode decays slowly, and the retention rate is 95.3%. After 200 charge and discharge cycles, the discharge capacity of the double ion gradient doped lithium-rich manganese-based layered transition metal oxide powder as the positive electrode decays slowly, and the retention rate is 91.2%. This shows that the material exhibits good electrochemical performance when used as the positive electrode of a lithium-ion battery.

[0039] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A dual ion gradient doped lithium-rich manganese-based layered transition metal oxide, characterized in that: The chemical formula of the oxide is xLi2MnO3·(1-x)LiTM 1-y M y O2, TM=one or more of Mn, Ni, Co, Fe or Cr, M=Sn and one of Mg, Ba, Zn or Ce, 0.01≤x≤0.5, 0.01≤y≤0.

3.

2. The dual ion gradient doped lithium-rich manganese-based layered transition metal oxide according to claim 1, characterized in that: The lithium-rich manganese-based layered transition metal oxide is prepared by uniformly mixing a transition metal compound precursor and a metal compound solution, adjusting the pH value of the mixed solution to 8-10 using an alkaline solution and continuously stirring, washing, filtering and drying to obtain a powder; heating the powder to 500-800° C., naturally cooling to room temperature, adding a lithium source and mixing uniformly, heating the mixture to 800-1000° C., and naturally cooling to room temperature.

3. The dual ion gradient doped lithium-rich manganese-based layered transition metal oxide according to claim 2, characterized in that: The metal compound solution is a mixed aqueous solution of Na2SnO4 and one of MgSO4, BaSO4, ZnSO4 and CeSO4.

4. The dual ion gradient doped lithium-rich manganese-based layered transition metal oxide according to claim 2, characterized in that: The transition metal compound precursor is a transition metal carbonate or a transition metal hydroxide; the particle size of the transition metal compound precursor is 5 to 10 μm.

5. The dual ion gradient doped lithium-rich manganese-based layered transition metal oxide according to claim 4, characterized in that: The transition metal carbonate is one or more of MnCO3, NiCO3, CoCO3, FeCO3 or CrCO3; the transition metal hydroxide is one or more of Mn(OH)2, Ni(OH)2, Co(OH)2, Fe(OH)2, or Cr(OH)2.

6. The dual ion gradient doped lithium-rich manganese-based layered transition metal oxide according to claim 2, characterized in that: The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium fluoride, lithium chloride or lithium nitrate.

7. The dual ion gradient doped lithium-rich manganese-based layered transition metal oxide according to claim 2, characterized in that: The molar ratio of the transition metal compound precursor to Li in the lithium source is 1:(1-10); the molar ratio of the transition metal compound precursor to the metal compound solution is 100:(0.1-5).

8. The dual ion gradient doped lithium-rich manganese-based layered transition metal oxide according to claim 2, characterized in that: The alkaline solution is one or more of aqueous ammonia, aqueous sodium carbonate solution or aqueous sodium bicarbonate solution.

9. The method for preparing the dual ion gradient doped lithium-rich manganese-based layered transition metal oxide according to any one of claims 1 to 8, characterized in that: The specific steps include: S1. The transition metal compound precursor and the metal compound solution are mixed uniformly, and the pH of the mixed solution is adjusted to 8 to 10 with an alkaline solution, stirred for 30 to 240 minutes, filtered and washed, and dried at 100 to 150 ° C to obtain a powder; S2. The powder is heated to 500-800°C and kept warm for 2-6 hours, then cooled to room temperature, a lithium source is added and mixed evenly, and then the mixture is heated to 800-1000°C and kept warm for 10-16 hours to obtain a dual-ion gradient doped lithium-rich manganese-based hierarchical transition metal oxide.

10. Application of the dual-ion gradient doped lithium-rich manganese-based layered transition metal oxide according to any one of claims 1 to 8 in the field of lithium-ion batteries or power batteries.

Citation Information

Patent Citations

  • Lithium-rich manganese-based cathode material and preparation method and application thereof

    CN110085827A

  • Surface layer gradient doped lithium-rich layered oxide positive electrode material as well as preparation method and application thereof

    CN111326730A

  • Concentration gradient doped lithium-rich manganese-based positive electrode material and preparation method thereof

    CN113213553A

  • Modified lithium-rich manganese-based LiaMnbMcXdYeO2-e material, preparation thereof and application of modified lithium-rich manganese-based LiaMnbMcXdYeO2-e material in lithium battery

    CN118738373A

  • Electronic device and operating method thereof

    KR1020250150388A